GLiMPSE - A Framework for Evaluating UX in Games - Carvalho, Vítor Marques; Furtado, Elizabeth Sucupira (Anais do Workshop sobre Interação e Pesquisa de Usuários no Desenvolvimento de Jogos (WIPlay); 2019: Anais do I Workshop sobre Interação e Pesquisa de Usuários no Desenvolvimento de Jogos, 2019)
The gaming industry has grown considerably in the last decades, designing experiences and interactive platforms through games, an entertainment media from the popular culture. With the advancement of technologies and user experience design methods, a challenge is faced for the constant improvement of the characteristics of a game aiming to improve the enjoyment and immersion perceived by users. To face this challenge, we designed a conceptual framework named GLIMPSE based on constructs used to evaluate user experiences with games. GLIMPSE brings together concepts of presence and interaction, goals, learning, context, and immersion used to evaluate experiences with games. Its applicability was tested through a questionnaire answered by 241 users from gaming forums and communities. The results provide insights revealing the GLIMPSE conceptual framework to be a useful tool for evaluating experiences in games by assessing the main UX elements and their existing overlap.